Peran Pengurus Dayah dalam Penyesuaian Diri Santri Baru di Dayah Darul Muta’allimin Desa Meulayo - Khairun Nadiya; Z Zalikha; A Azhari (Journal of Current Research in Management, Policy, and Social Studies, 2024)
The purpose of this research is to determine the role of the Dayah administrators in the adjustment of new students as well as the support and obstacles that Dayah administrators have in the adjustment of new students. The method used is descriptive analysis with a qualitative approach. The data collection techniques use observation, interviews and documentation. In this research, the sample was taken using a purposive sampling technique, the subjects in this research were 10 people, namely 6 Dayah administrators and 4 new students. The results of the research show that the Dayah administrators play an important role in the adjustment of new students, acting as parents, teachers and friends who guide and direct the new students. There is support for the Dayah administrators when new students comply with time management, cooperation with the students' parents and the new students' firm stance. Meanwhile, the obstacle is when students are reluctant to tell stories, they tend to keep silent about their feelings that the students don't get a solution. Apart from that, new students are often allowed to go home due to illness and various reasons, making it difficult for the students to adapt to the habits and regulations of Dayah Darul Muta'allimin.